Strategi Pemasaran Produk Minyak Sacha Inchi (Studi Kasus di IKM Quilla Herbal Indonesia Sejahtera) - Rahmawati, Salsa Idha; Nugraha, Adi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
IKM Quilla Herbal Indonesia Sejahtera is a herbal company specializing in the production of sacha inchi oil derived from processed sacha inchi. However, the sales of sacha inchi oil within the company have shown instability and tended to stagnate between 2022 and 2023. Therefore, it is imperative to pinpoint the underlying cause to devise an effective marketing strategy aimed at boosting the sales of sacha inchi oil products. The research employed qualitative method with a case study technique. Primary and secondary data were gathered through observation, interviews involving key informants including company personnel and managers. Data were analyzed by using Strength, Weakness, Opportunity & Threat (SWOT) analysis and Quantitative Strategic Planning Matrix (QSPM) analysis. The research findings reveal the existence of eight alternative strategies: 1) Implementing monthly evaluations coupled with data analysis, 2) Collaborating with health experts, 3) Leveraging connections with governmental bodies and universities, 4) Engaging in direct marketing initiatives, 5) Harnessing the power of artificial intelligence (AI), 6) Enhancing workforce capabilities, 7) Optimizing content and targeting social media, and 8) Forming strategic partnerships. Among these alternatives, the priority strategy with the highest value is conducting monthly evaluations coupled with data analysis.